Compelled to write: alternative rhetoric in theory and practice - Wallace, David L., author; Utah State University Press, publisher (Colorado State University. Libraries, 2011)
David Wallace argues that any understanding of writing studies must include the conception of discourse as an embodied force with real consequences for real people. Informed in important ways by queer theory, Wallace calls to account users of dominant discourses and at the same time articulates a theory base from which to interpret "alternative rhetoric." To examine the practice of writing from varied margins of society, Compelled to Write offers careful readings of four exemplar American writers, each of whom felt compelled within their own time and place to write in response to systemic injustices in American society. Sarah Grimké, a privileged white woman advocating for abolition, is forced to defend her right to speak as a woman Frederick Douglass begins his public career almost as a curiosity (the articulate ex-slave) and ends it as one of the most important rhetors in American history Gloria Anzaldúa writes not only in multiple languages and dialects but from marginalized positions related to gender, race, class, sexual identity, and physical abled-ness David Sedaris uses his privileged position as a middle-class white male humorist to speak unabashedly of his sexuality, his addictions, and obsessive-compulsive personality disorder. Through these writers, Wallace explores a range of strategies that comprise alternative rhetorical practice, and demonstrates how such practice is inflected by social constraints on rhetorical agency and by how writers employ alternative discourses to resist those constraints. Grounding and personalizing Compelled to Write with rich material from his own teaching and his own experience, Wallace considers a number of implications for teachers of writing.
1: Defining Alternative Rhetoric: Embracing Intersectionality and Owning Opacity Interchapter: Piano Lessons -- 2: Sarah Grimké: Breaking the Bonds of Womanhood Interchapter: Jumper Cables and Double Consciousness as a Habit of Mind -- 3: Frederick Douglass: Taking an Ell to Claim Humanity Interchapter: Pickles -- 4: Gloria Anzaldúa: Borderlands and Fences Literacy and Rhetoric Interchapter: The Light of the World -- 5: David Sedaris: Expanding Epideictic-A Rhetoric of Indirection Interchapter: Day Four in Paris -- 6: Alternative Rhetoric and Marked Writing.
Keywords: English language -- Rhetoric; Discourse analysis, Literary